Modeled Mega Impact Structures In Paraguay: II- Eastern Region - Presser, Jaime L. B. (2016)
We report here the discovery and study of several new modeled large impact craters in Eastern Paraguay, South America. They were studied by geophysical information (gravimetry, magnetism), field geology and also by microscopic petrography. Clear evidences of shock metamorphic effects were found (e.g., diaplectic glasses, PF, PDF in quartz and feldspar) at 4 of the modeled craters: 1) Negla: diameter:~80-81 km., 2) Yasuka Renda D:~96 km., 3) Tapyta, D: ~80 km. and 4) San Miguel, D: 130-136 km. 5) Curuguaty, D: ~110 km. was detected and studied only by geophysical information. Target-rocks range goes from the crystalline Archaic basement to Permian sediments. The modeled craters were in some cases cut by tholeiitic/alkaline rocks of Mesozoic age and partially covered by lavas of the basaltic Mesozoic flows (Negla, Yasuka Renda, Tapyta andCuruguaty). One of them was covered in part by sediments of Grupo Caacupé (age: Silurian/Devonian). Some of these modeled craters show gold, diamonds, uranium and REE mineral deposits associated. All new modeled large impact craters are partially to markedly eroded.